PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENYUSUNAN PERATURAN DESA PARTISIPATIF DI MOJOLABAN - Sudibyo, Bambang Joko (PARENTAL, 2013)
The results of research show that the role of the Consultative Body (BPD) in village governance system serves as a village legislature stipulated in Law No. 32 of 2004, Regulation of the Government (PP) No. 72 of 2005, and Sukoharjo District Regulation (Perda) No. 6 of 2006 . BPD instrumental set rules with the village chief, the community and share their aspirations. The mechanism of the Village formally procedural regulations include: (a) Preparation Establishment of Village Regulations; (b) Discussion of Draft Regulation Village; (c) Establishment of Village Regulations and Endorsements; (d) Rural Development and Control Regulations; (e) The promulgation and dissemination Village regulations. Factors affecting the preparation of the implementation of Regulation participatory village in the district consists of 5 factors Mojolaban the juridical, political, human resources BPD, Facilities/Information Technology Facilities and rural culture.Alpha